Language and cognitive outcomes after childhood stroke: Theoretical implications for hemispheric specialization. (November 2019) - de Montferrand, Camille; Vassel-Hitier, Jeanne; Yvon-Chaou, Estelle; Câmara-Costa, Hugo; Dellatolas, Georges; Chevignard, Mathilde
Abstract: The purpose of this study was to investigate language and cognitive outcomes following severe childhood stroke, and the role of age at stroke according to lesion lateralization. We retrospectively included children consecutively admitted to a physical medicine and rehabilitation department between 1992 and 2015 following childhood stroke (age at stroke 1 month to15 years). Data collection included demographic and clinical information, results of cognitive assessments on the Wechsler Intelligence scales, detailed language assessments by speech and language therapists, and long-term academic outcome. Overall, 184 children (52% boys; mean age at assessment = 8.5 years, range .7–15.4 years) were hospitalized following ischemic ( n = 79) or hemorrhagic ( n = 105) stroke. After a median time since stroke of 4 months ( n = 135), mean Full-Scale, Verbal, and Performance Intellectual Quotient (FSIQ, VIQ and PIQ) were 85 (SD = 19), 93 (SD = 22), and 85 (SD = 20), respectively. In language tests ( n = 130) assessing lexical and syntactic expression and comprehension, 26%–53% of the children exhibited impairments (scores <2SD). After a median follow-up of 40 months, only 27% of the children were following a normal curriculum without adaptations or delay, and 27% were attending special education programs. School situation was strongly associated with language and FSIQ scores. Language and verbal IQ scores were significantly lower ( p < .01) among patients with lesions in the left hemisphere as opposed to the right. After a left hemisphere lesion, language skills were not associated with age at stroke, but for right hemisphere lesions, language was more impaired among children who were younger at stroke onset. PIQ tended to correlate positively with age at stroke in left hemisphere lesions (poorer PIQ in early lesions) and negatively for right hemisphere lesions (poorer PIQ in late lesions). These findings, discussed in the light of the brain vulnerability and plasticity hypotheses, are in favor of a developmental view of hemispheric specialization.